2005
DOI: 10.1038/sj.ejhg.5201422
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of NOS2A promoter polymorphisms in Australian multiple sclerosis patients

Abstract: As with other major autoimmune diseases, susceptibility to multiple sclerosis (MS) is believed to result from the complex interaction of a number of genes, each with modest effect. Extensive research of experimental autoimmune encephalomyelitis in mice and several direct MS studies have implicated NOS2A, which encodes the inducible form of nitric oxide synthase, and the genetic region encoding NOS2A, 17q11.2, has been identified in a number of genome wide screens as being potentially associated with MS. We inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
1
7
1
Order By: Relevance
“…Finally, given the importance of DRB1*15 in MS, we stratified families based on carrier status of this risk allele for analyses of all NOS2A SNPs and haplotypes to look for differences. Previous results suggested NOS2A associations were more prominent in DRB1*15-positive MS cases 20,21 and/or families, however the current study does not confirm this finding.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Finally, given the importance of DRB1*15 in MS, we stratified families based on carrier status of this risk allele for analyses of all NOS2A SNPs and haplotypes to look for differences. Previous results suggested NOS2A associations were more prominent in DRB1*15-positive MS cases 20,21 and/or families, however the current study does not confirm this finding.…”
Section: Discussioncontrasting
confidence: 99%
“…20 Evidence for excess transmission of the T allele remained significant even after correction for multiple testing in HLA-DRB1*15-positive families. Because the associated SNP confers a synonymous coding change, and other smaller NOS2A studies in MS have either suggested trends 21,22 or failed to detect an association, [23][24][25] much larger studies are needed to confidently confirm or exclude a role for this important locus in disease susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with previous work (Bugeja et al, 2005) and is to be expected given the close proximity of the SNPs, the relatedness of the Norfolk population and the prevalence of the minor SNP allele (410%). With the exception of the À1026/ À1659 marker pair, all the SNPs studied in the Norfolk population were found to be in complete and significant LD with each other.…”
Section: Resultssupporting
confidence: 81%
“…Further negative results derived from an Australian study of 4 SNPs in the same gene promoter region, although a trend to significance suggested an interaction between the studied NOS2A promoter polymorphisms and the HLA-DRB1 ⁎ 1501 genotype in predisposing to MS [21].…”
Section: Discussionmentioning
confidence: 97%
“…A multilocus genotyping assay provided evidence for a strong linkage and association between the NOS2A locus and MS [6], although 4 independent casecontrol studies failed to demonstrate further association with several polymorphisms located in the promoter region of the NOS2A gene [18][19][20][21].…”
Section: Introductionmentioning
confidence: 95%